2022
DOI: 10.3390/jmse10111692
|View full text |Cite
|
Sign up to set email alerts
|

Increased Temperature and Nitrogen Enrichment Inhibit the Growth of the Golden Tide Blooming Macroalgae Sargassum horneri in the Yellow Sea, China

Abstract: The golden tide, a large biomass bloom of the brown macroalgae Sargassum horneri, occurs yearly in the Yellow Sea, where it causes enormous economic and ecologic losses. To investigate the response of S. horneri to global warming and eutrophication, S. horneri was cultured under six conditions of varying temperature combinations (20 and 24 °C) and nitrogen levels (5, 30, and 300 μM). The growth, photosynthetic performance, pigment content, and contents of soluble protein were assessed. The growth of S. horneri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The nitrogen content of 50 µmol L −1 in natural seawater was observed in the sampling sites, and in previous research, it was reported that the inorganic nitrogen content in golden tide bloom area increased by 3-4 times [19]. In all the treatments, the concentration of inorganic phosphorus (P) was set to 10 µmol L −1 through the addition of KH2PO4 to avoid P limitation [20,21]. Other conditions were the same as the temporary culture, and the seawater medium was renewed every two days.…”
Section: Experimental Designmentioning
confidence: 84%
“…The nitrogen content of 50 µmol L −1 in natural seawater was observed in the sampling sites, and in previous research, it was reported that the inorganic nitrogen content in golden tide bloom area increased by 3-4 times [19]. In all the treatments, the concentration of inorganic phosphorus (P) was set to 10 µmol L −1 through the addition of KH2PO4 to avoid P limitation [20,21]. Other conditions were the same as the temporary culture, and the seawater medium was renewed every two days.…”
Section: Experimental Designmentioning
confidence: 84%
“…ESS1 ( Kishimoto et al., 2019 ; Khoa et al., 2021 ). Since heat stress generally reduces nitrogen uptake and growth in algae ( Gerard, 1997 ; Hay et al., 2010 ; Gouvêa et al., 2017 ; Endo et al., 2020 ; Fernández et al., 2020 ; Wu et al., 2022 ), it is important to address whether the establishment of heat stress memory modulates the uptake of nitrogen sources under heat stress conditions in algae. Therefore, in this study, we identified ‘ Bangia ’ sp.…”
Section: Discussionmentioning
confidence: 99%
“…High temperature usually inhibits the growth of macroalgae ( Endo et al., 2020 ; Fernández et al., 2020 ; Wu et al., 2022 ). In addition, high temperature reduces nitrogen uptake and nitrogen content in these algae ( Gerard, 1997 ; Hay et al., 2010 ; Gouvêa et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation